Penentuan Komoditas dan Kawasan Unggulan Subsektor Perkebunan - Ridanil Hanif,; Restuhadi, Fajar; Arifudin, Arifudin (JURNAL AGRIBISAINS, 2023)
In the context of regional development, regional development directions are needed based on the availability of resources, so that regional development directions can be directed and run well. In general, the goals of regional development are equity, economic growth, and sustainability so that the region can develop to the desired level. The ability to take advantage of the potential planning resources available in the region is a way of developing a region based on regional potential. One of the solutions in regional development is the development of superior commodities, with the intention that these commodities can support regional economic growth and people's welfare. The purpose of this study was to identify and determine the superior commodities of the plantation sub-sector in Rokan Hulu Regency and to determine the location of the superior production of the plantation sub-sector in Rokan Hulu Regency. Leading commodities are determined based on analysis of Sectoral Contribution Index (SCI), Growth Ratio Model (GRM), Dynamic Location Quotient (DLQ), Location Quotient (LQ) and Composite Indeks (CI). Meanwhile, plantations in plantation sub-sector superior production areas are carried out using a Geographic Information System with Hot Spot analysis Getis-Ord Gi*. Based on the results of the analysis, it is known that the leading commodities in the plantation sector in Rokan Hulu Regency are rubber and palm oil. Hot Spot analysis shows the location of the leading area, namely in North Tambusai District. The results of this study are expected to be input in determining the superior commodities of plantation estates and the development of agropolitan areas in Rokan Hulu Regency.